STYROFOAM UTILIZATION IN THE SYNTHESIS OF SOLID POLYELECTROLYTES PSS-LICLO4-PHB FOR LITHIUM BATTERY APPLICATIONS - INSYANI, RIZKI
Recently human requires to access information, technology and communications quickly. Therefore, the need for portable electronic devices becomes very important. Because of the existence of supporting power / energy supplier in the form of lithium-ion batteries, portable electronic devices can be operated well. However, the use of lithium battery that is not good can cause leakage of electrolyte fluid of LiClO4, harmful to the environment, and also high self-discharge. This problem can be treated with the discovery of solid polymer electrolyte. Preparation of polyelectrolyte that is friendly environmentally is required to decrease the risk of environmental pollution caused by toxic materials of battery components. Therefore, in this study was focused on the preparation of environmentally friendly polyelectrolyte membrane with low cost for lithium-ion battery applications. The preparation of polyelectrolyte membrane was done by casting of polymer solution. The main materials used to prepare polyelectrolyte membranes are polystyrene obtained from isolation of styrofoam, hydrolyzed bacterial poly(R-hydroxybutyrate) (PHB) and lithium perchlorate (LiClO4) as ionic salt. First polystyrene was reacted with acetyl sulfate to form sulfonated polystyrene (PSS). These three main materials were mixed and dissolved in an appropriate solvent, the mixture of polymer solution was poured into a petri dish, and then their solvent was evaporated. Molecular weights of polymers were determined by viscometry method, and molecular weights of PS, PSS, and PHB were obtained about 178,175; 236,060; and 92,000 g/mol, respectively. The sulfonation degree of polystyrene (PSS) prepared by reaction with acetyl sulfate at 40oC for 30 minutes was 14,6 %. The solid membranes of PSS-LiClO4-PHB were characterized by analysis of functional groups (FTIR), mechanical strength (Tensile tester Instron), conductivity (Electrochemical Impedance Spectroscopy (EIS), and surface morphology (Optical microscope). The measurement results show that the increase of LiClO4 content in the membranes, the conductivity and mechanical strength of membranes increase, but the surface morphology of membrane become less uniform and homogenous.